Seed banks as incidental fungi banks: Fungal endophyte diversity in stored seeds of banana wild relatives - Hill, Rowena; Llewellyn, Theo; Downes, Elizabeth; Oddy, Joseph; MacIntosh, Catrona; Kallow, Simon; Panis, Bartholomeus; Dickie, John B.; Gaya, Ester (Frontiers Media, 2021)
Seed banks were first established to conserve crop genetic diversity, but seed banking has more recently been extended to wild plants, particularly crop wild relatives (CWRs) (e.g., by the Millennium Seed Bank (MSB), Royal Botanic Gardens Kew). CWRs have been recognised as potential reservoirs of beneficial traits for our domesticated crops, and with mounting evidence of the importance of the microbiome to organismal health, it follows that the microbial communities of wild relatives could also be a valuable resource for crop resilience to environmental and pathogenic threats. Endophytic fungi reside asymptomatically inside all plant tissues and have been found to confer advantages to their plant host. Preserving the natural microbial diversity of plants could therefore represent an important secondary conservation role of seed banks. At the same time, species that are reported as endophytes may also be latent pathogens. We explored the potential of the MSB as an incidental fungal endophyte bank by assessing diversity of fungi inside stored seeds. Using banana CWRs in the genus Musa as a case-study, we sequenced an extended ITS-LSU fragment in order to delimit operational taxonomic units (OTUs) and used a similarity and phylogenetics approach for classification. Fungi were successfully detected inside just under one third of the seeds, with a few genera accounting for most of the OTUs–primarily Lasiodiplodia, Fusarium, and Aspergillus–while a large variety of rare OTUs from across the Ascomycota were isolated only once. Fusarium species were notably abundant–of significance in light of Fusarium wilt, a disease threatening global banana crops–and so were targeted for additional sequencing with the marker EF1α in order to delimit species and place them in a phylogeny of the genus. Endophyte community composition, diversity and abundance was significantly different across habitats, and we explored the relationship between community differences and seed germination/viability. Our results show that there is a previously neglected invisible fungal dimension to seed banking that could well have implications for the seed collection and storage procedures, and that collections such as the MSB are indeed a novel source of potentially useful fungal strains.